LncRNA PCIR Is an Oncogenic Driver via Strengthen the Binding of TAB3 and PABPC4 in Triple Negative Breast Cancer - Guo, Wenhui; Li, Jingyi; Huang, Haobo; Fu, Fangmeng; Lin, Yuxiang; Wang, Chuan (Frontiers in Oncology, 2021)
Long non-coding RNAs (LncRNA) as the key regulators in all stages of tumorigenesis and metastasis. However, the underlying mechanisms are largely unknown. Here, we report a lncRNA RP11-214F16.8, which renamed Lnc-PCIR, is upregulated and higher RNA level of Lnc-PCIR was positively correlated to the poor survival of patients with triple negative breast cancer (TNBC) tissues. Lnc-PCIR overexpression significantly promoted cell proliferation, migration, and invasion in vitro and in vivo. RNA pulldown, RNA immunoprecipitation (RIP) and RNA transcriptome sequencing technology (RNA-seq) was performed to identify the associated proteins and related signaling pathways. Mechanistically, higher Lnc-PCIR level of blocks PABPC4 proteasome-dependent ubiquitination degradation; stable and highly expressed PABPC4 can further increase the stability of TAB3 mRNA, meanwhile, overexpression of Lnc-PCIR can disrupt the binding status of TAB3 and TAB2 which lead to activate the TNF-α/NF-κB pathway in TNBC cells. Our findings suggest that Lnc-PCIR promotes tumor growth and metastasis via up-regulating the mRNA/protein level of TAB3 and PABPC4, activating TNF-α/NF-κB signaling pathway in TNBC.